Co-sputtering NbTiN thin films on PSG/Si substrates. (16th December 2015) - Wang, Chen; Zhang, Jingjiao; Zhang, Lu; You, Lixing; Su, Xiaodong
Abstract: Single-crystalline silicon is one of a few promising substrate materials on which to grow NbTiN ultrathin films for applications in superconducting single photon detection devices. In this work, a buffer layer of phosphorus silicate glass (PSG) ∼250 nm is formed rapidly on the silicon substrate under a relatively low temperature to ease the mismatching between NbTiN and substrate, and simultaneously act as an antireflection layer at the working wavelength. (111)-oriented NbTiN films were deposited on both SiO2 /Si and PSG/Si substrates by using a dc reactive magnetron co-sputtering system of independent Nb and Ti targets. The superconducting critical temperature T c of the 5 nm-NbTiN/PSG/Si sample reaches ∼8.8 K due to effectively relieving the mismatch between NbTiN and Si by PSG buffer layer.